PENGARUH KEMUDAHAN PENGGUNAAN, MANFAAT DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN E-PAYMENT QRIS PADA GENERASI Z - Octaviani, Leonarda Sukacita; Pranatasari, Fransisca Desiana; Maridjo, H. Hery (Ma Chung Press, 2024)
The use of QRIS-based electronic money has become very popular as a non-cash payment system because society has shifted to non-cash payments. This study aims to determine the influence of ease of use, benefits, and trust on the interest in using QRIS e-payment. The research method used is descriptive quantitative. The population in this study includes all Generation Z individuals who have used QRIS e-payment in the past year and reside in the Special Region of Yogyakarta. The sampling technique employed is purposive sampling, with a sample of 96 Generation Z individuals who have used QRIS e-payment. The instrument testing technique includes validity and reliability tests. Data analysis uses multiple linear regression, and data processing is conducted with IBM SPSS Statistics 26. The results of this study indicate that ease of use does not affect the interest in using QRIS e-payment, benefits affect the interest in using QRIS e-payment, and trust affects the interest in using QRIS e-payment.